Relationship between Interpersonal Skills in Project Success - Naseem, Aliya; Abbas, Rameesha (Archives of Business Research, 2022)
The most asset to any project, regardless of the industry is the project manager. Research has shown whether the project fails or succeeds depends on the project manager, and the skills they bring to the table. The research problem in this study is the lack of research regarding the relationship between the interpersonal skills of the project manager and the success and / or failure of large-scale IT systems development projects. The existing literature indicated a strong positive relationship between the interpersonal skills and leadership traits of senior managers who manage with a passive leadership style and the primary IT systems development project success factor of cost. There was also a strong positive relationship between the interpersonal skills and leadership traits of senior managers who manage with leadership outcomes and the primary IT systems development project success factor of scheduling.